Color Image Retrieval Based on Chernoff Distance Measure - Selvaraj, S; Seetharaman, K (International Journal of Computer Sciences and Engineering, 2018)
This paper proposes a novel technique, based on distributional approaches with distance measure, i.e. Chernoff distance measure. Since the proposed system is automatic retrieval, it is difficult to understand the nature of the query and target images and which distribution they follow. The Chernoff distance measure overcome this problem, because it adapts itself accordingly the nature of the images, viz. the Chernoff distance could be adapted though the query and target images do no distributed to Gaussian or mixed or even if they are distribution free. This is the main advantage of the proposed technique. In order to examine the proposed technique, an image database is constructed, which contains variety of images such as texture, structure, blurred, noise, artifacts images and their features.